Implosão e explosão na exópolis: evidências a partir do mercado imobiliário da RMBH - Renan Pereira Almeida (2015)
Among the spatial phenomena of the contemporary metropolis, the so-called Implosion and Explosion, derived from the Henri Lefebvres work, are highlighted in this work. Implosion is interpreted as a trend to agglomeration in metropolis central areas meaning revitalization or crystallization of these areas as privileged spaces. Explosion enlightens a broad process of extended urbanization, which indicates occupation of areas far away from the main centralities, urban sprawl and growth in the metropolitan fringes. These two spatial trends are related to Exopolis, an interpretation of the contemporary metropolis given by Edward W. Soja. The occurrence of these two phenomena was empirically tested to Belo Horizonte and its metropolitan area, MABH, through housing market data. To achieve this goal, LISA (Local Indicators of Spatial Association) and Fuzzy Clustering Analysis were used, using data provided by Tax on Transfer of Real Estate (TTRE) to Belo Horizonte in the case of implosion, and by the site Net Imóveis to MABH in the case of explosion. The results were inconclusive to implosion hypothesis when considered the whole central area (defined as the area inside Contorno Avenue), due to the internal heterogeneity of this area, fundamentally. In the case of explosion, the MABHs housing market provided evidences on its expansion by the region, as clusters of houses for workers in the urban fabric as well as spaces intended for elites via gated condominiums.